2021
DOI: 10.1007/s41999-021-00582-5
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to completing the 4AT for delirium and its clinical implementation in two hospitals: a mixed-methods study

Abstract: Purpose To assess the clinical implementation and barriers to completing the 4AT for delirium in general medical and geriatric patients over 75 years upon admission to Wellington and Kenepuru Hospitals during the first eight months of 2017, 2018 and 2019. Methods Retrospective data from electronic health records were analysed using an explanatory-sequential mixed-methods approach. The initial quantitative phase measured doctors’ adherence to the 4AT and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(24 citation statements)
references
References 43 publications
1
20
0
1
Order By: Relevance
“…The 4AT had positive score rates which were broadly consistent with estimated rates of delirium in the populations concerned. The present positive score rates are comparable with recent studies using the 4AT [ 46 ] and the Nursing Delirium Screening Scale [ 47 ] and contrast with the lower positive score rates reported in large scale studies using the CAM [ 15 , 18 , 20 , 21 ]. The study also has some limitations.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…The 4AT had positive score rates which were broadly consistent with estimated rates of delirium in the populations concerned. The present positive score rates are comparable with recent studies using the 4AT [ 46 ] and the Nursing Delirium Screening Scale [ 47 ] and contrast with the lower positive score rates reported in large scale studies using the CAM [ 15 , 18 , 20 , 21 ]. The study also has some limitations.…”
Section: Discussionsupporting
confidence: 86%
“…By contrast, in hip fracture care in England, assessment of delirium with the 4AT is mandated and incentivised as part of the Best Practice Tariff, and completion rates are >95% [ 27 ]. These and other studies [ 46 , 47 ] suggest that delirium assessment at scale in routine clinical workflow is possible but that achieving this requires appropriate data collection, and visibility, policy and education.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Only three studies reported specifically on patients without a completed assessment. 18,21,22 In a study using the 4AT, patients without an assessment had similar outcomes to patients with probable cognitive impairment, 22 whilst in a study using the CAM, patients "unable to assess" had worse outcomes than patients with delirium. 18 This concerning observation highlights the importance of elucidating barriers to delirium assessment.…”
Section: Summary Of Main Findingsmentioning
confidence: 99%
“…Prinzipiell ist es zielführend, einen Test zu nutzten, der für die Notaufnahme validiert ist. Zusätzlich ist es sinnvoll, wenn möglich einen bereits in der Klinik implementierten Test zu nutzen, da sich die Performance eines Tests durch mangelndes Wissen oder andere Barrieren erhöht [23].…”
Section: Merkeunclassified